The practices of good governance in National Solid Waste Management Policy (NSWMP) implementation: a case study of Kuala Lumpur, Malaysia - Abas, Muhamad Azahar; Wee, Seow Ta; Chen, Goh Kai (American Scientific Publishers, 2018)
An efficient solid waste management is crucial. Inefficient solid waste management would cause a huge obstacle in social development, environmental vitality, and economic stability. Therefore, a progressive policy is necessary to improve solid waste management. The National Solid Waste Management Policy (NSWMP) was introduced in 2007 under the Act 672. The execution of NSWMP involves stakeholders from various government agencies and a collaboration with the private sectors. Despite the initiatives taken by the stakeholders, the objectives of NSWMP failed to materialise. One of the major constraints is weak governance among stakeholders with regards to the NSWMP implementation. This paper will explore the good governance practices implemented by the stakeholders. Identifying the current good governance practices implemented by the stakeholders is crucial as it will serve as a guideline to improve good governance practice in the future. An exploratory research approach is applied in this study through in-depth interviews with several government agencies and concessionaires involved in the NSWMP implementation at Kuala Lumpur. A total of six respondents took part in this study. The findings of this study show that there are several good governance practices implemented in policy promotion, participation of stakeholders, and capacity enhancement programme for the staff. This study also proposed some points on good governance practices in the context of policy promotion and staff development. A paradigm shift by the stakeholders is imperative so as to enhance the good governance practice in NSWMP implementation towards an efficient solid waste management in Malaysia.